2013
DOI: 10.1007/s10565-013-9260-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induces cell cycle arrest and triggers apoptosis via Sp1-dependent p75NTR expression in human neuroblastoma cells

Abstract: Ethanol exposure has deleterious effects on the central nervous system. Although several mechanisms for ethanol-induced damage have been suggested, the precise mechanism underlying ethanol-induced neuronal cell death remains unclear. Recent studies indicate that the p75 neurotrophin receptor (p75NTR) has a critical role in the regulation of neuronal survival. This study was designed to examine the role of p75NTR in ethanol-induced apoptotic signaling in neuroblastoma cells. Ethanol caused highly increased leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…As clearly indicated in our paper (Marzotto et al, 2014), the final ethanol concentration was 0.03% v/v (p. 2), and “no significant differences in cell viability were observed between cells treated with the ethanol control solution 0.03% (v/v) and untreated cells” (p. 5). Furthermore, as other researchers have found (Do et al, 2013), cell viability of neurocytes is unaffected by doses of ethanol up to 10 mmol/L (0.06%). Low doses of ethanol may influence gene expression, but would have acted in the same way in the Gelsemium and in the control samples.…”
supporting
confidence: 72%
“…As clearly indicated in our paper (Marzotto et al, 2014), the final ethanol concentration was 0.03% v/v (p. 2), and “no significant differences in cell viability were observed between cells treated with the ethanol control solution 0.03% (v/v) and untreated cells” (p. 5). Furthermore, as other researchers have found (Do et al, 2013), cell viability of neurocytes is unaffected by doses of ethanol up to 10 mmol/L (0.06%). Low doses of ethanol may influence gene expression, but would have acted in the same way in the Gelsemium and in the control samples.…”
supporting
confidence: 72%
“…The results of monoclonal phage-ELISA indicated that all clones had principally bound to NTRK2 (binding affinity above 2.1), as shown in Figure 3. Clones 1, 3, 10, 14,16,17,19,20,22,23,24,28,30,31, and 32 were selected as strongly positive phage plaques for sequencing and further analysis (quadruple asterisks with a significant difference in Figure 3).…”
Section: Peptide Specificity and Activity Assaymentioning
confidence: 99%
“…It was reported that the activation of JNK reduced cell proliferation by elevation of the expression of cyclin‐dependent kinase inhibitor (cell‐cycle inhibitor) p21 in neuroblastic cells [Haeusgen et al, ]. Coincident with this report, p75 receptor is engaged in the suppression of neuroblastoma cell growth by p21 induction [Do et al, ]. Moreover, p75 also regulates other cell‐cycle inhibitors, p27 and Rb, to block the proliferation of gastric cancer cells [Jin et al, ].…”
Section: Discussionmentioning
confidence: 73%